Antecedents and outcomes of retailer reputation: Evidence from an emerging economy - Rajić, Tamara; Nikolić, Ivan; Milošević, Isidora (Industrija, 2017)
Over prevous years the construct of corporate reputation has received much attention among academics and business practitioners. Whereas researchers’ interests have been mainly pointed to the implications of good corporate reputation, its antecedents have largly been understudied. Moreover, majority of previous research took part in the context of the U.S. and Western Europe, leaving service industries in emerging economies rather neglected area. Hoping to fill this void in marketing knowledge, the objective of this study is to propose and empirically examine a model of retailer reputation, by incorporating the construct into the framework of established relationships among key service evaluation constructs. Conceptual model has been examined on a sample of Serbian grocery retail customers by means of structural equation modelling (SEM). Results of the study point to significant effect of service quality and value on retailer reputation and the direct impact of reputation on customer loyalty. Limitations of the study have been discussed and directions for future research are provided.